2017
DOI: 10.18203/2394-6040.ijcmph20172858
|View full text |Cite
|
Sign up to set email alerts
|

A study on knowledge regarding first aid among undergraduate medical students

Abstract: Background: Life is characterized by precarious twists and turns and risky conditions that emerge all the time. First aid is the immediate action taken to save a life and reduce the effects of injury and illness until medical help is obtained. This study aims at assessing the knowledge regarding first aid among undergraduate medical students and comparing the knowledge among different terms. Methods: A cross-sectional study was done among 150 undergraduate medical students of Vydehi Medical College, Bangalore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The students included 3 different faculties with 33.3% (74) from pharmacy faculty, 32.9% (73) from dental faculty, and 33.8% (75) from medical faculty. Overall, the medical students recorded the most correctly answered questions in comparison to students from the pharmacy and dental schools, indicating that there is a significant difference in knowledge among the 3 faculties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The students included 3 different faculties with 33.3% (74) from pharmacy faculty, 32.9% (73) from dental faculty, and 33.8% (75) from medical faculty. Overall, the medical students recorded the most correctly answered questions in comparison to students from the pharmacy and dental schools, indicating that there is a significant difference in knowledge among the 3 faculties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table (1) presented that 83.3 percent of the second stage students and 96.6 of the fourth stage nursing students were within age group (19 -24) years old. Moreover, 76.6 percent of the second stage and 80 percent of the fourth stage were male.…”
Section: Resultsmentioning
confidence: 96%
“…Results in Table (1) presented that most of the study sample were male nursing students in both the second and fourth stage within the age group of (19 -24) years old. In addition, nursing students of both groups had not participated in any educational program or training sessions related to first aid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Similarly In Bangalore, India, the association between year of study and level of knowledge was found to be statistically significant. 15 The study contained questions regarding the circulatory system, respiratory system, toxicology, burn management, fracture handling and shock state management. The results showed that the students had better understanding regarding the theoretical aspects of first aid rather than the practical implementation.…”
Section: Discussionmentioning
confidence: 99%